Proton-coupled electron transfer in a hydrogen-bonded charge transfer complex - Verma, Sandeep; Aute, Sunil; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry B, 2016)
A proton-coupled electron transfer (PCET) reaction in a hydrogen bonded charge-transfer (CT) complex of 4-([2,2'-bipyridin]-4-yl)phenol (bpy-phenol) with a F- ion has been investigated by ultrafast time-resolved transient absorption spectroscopy. The phenolic receptor molecule, bpy-phenol, binds to the F- ion through a hydrogen bond and senses the F- ion-via the Stokes-shifted CT band. Upon photoexcitation, CT from the phenol residue to the bpy residue promotes proton transfer from the phenol radical cation (ArOH center dot+) to the fluoride ion at ultrafast time scales of <150 fs (instrument response function limited) and 3 ps, separately. The fast and slow proton-transfer times are linked to two different types of hydrogen-bonding networks between the phenol residue and fluoride ion. Crystalline water in the fluoride salt hydrates mediates the proton-transfer reaction. This work demonstrates the participation of a hydrogen-bonded water bridge within a PCET reaction in a water restricted environment.

Photo-induced cytotoxicity and anti-metastatic activity of ruthenium(II)-polypyridyl complexes functionalized with tyrosine or tryptophan - Ramu, Vadde; Aute, Sunil; Taye, Nandaraj; Guha, Rweetuparna; Walker, Michael G.; Mogare, Devaraj; Parulekar, Apoorva; Thomas, Jim A.; Chattopadhyay, Samit; Das, Amitava (Dalton Transactions, 2017)
The synergistic effect of oxygen, light, and photosensitizer (PS) has found applications in medicine for the treatment of cancer through photodynamic therapy (PDT). Induction of apoptosis to cancerous cells will prevent tumor metastasis that spreads cancer cells to the neighboring organs/tissues. Herein, we report the two apoptotic Ru(II)-polypyridyl complexes that are functionalized with pendant amino acid moieties tyrosine (1) and tryptophan (2), respectively. These two water soluble complexes were found to interact strongly (K-a(1) = (1.18 +/- 0.28) x 10(5) M-1 and K-a(2) = (1.57 +/- 0.77) x 10(5) M-1) with CT-DNA. Isothermal titration calorimetry (ITC) studies revealed that these complexes bind to CT-DNA through an entropically driven process. Both the complexes showed photo-induced cytotoxicity and exhibit apoptotic activity under photo-irradiation conditions. The comet assay indicated that these complexes can damage cellular DNA, which is attributed to the significant build-up of O-1(2) level even on irradiation with low intensity light (10 J cm(-2), lambda(Range) 450-480 nm). This photoinduced DNA damage and apoptosis in A549 cells was induced by reactive oxygen species (ROS) and occurred through up-regulation of apoptotic marker caspase-3. Control experiments under dark conditions revealed an insignificant cytotoxicity towards these cells for two photosensitive molecules.

Proton-coupled electron-transfer processes in ultrafast time domain: evidence for effects of hydrogen-bond stabilization on photoinduced electron transfer - Dey, Ananta; Dana, Jayanta; Aute, Sunil; Maity, Partha; Das, Amitava; Ghosh, Hirendra N. (Chemistry-A European Journal, 2017)
The proton-coupled electron-transfer (PCET) reaction is investigated for a newly synthesized imidazoleanthraquinone biomimetic model with a photoactive RuIIpolypyridyl moiety that is covalently coupled to the imidazole fragment. Intramolecular H-bonding interactions between imidazole and anthraquinone moieties favor the PCET process; this can be correlated to an appreciable positive shift in the one-electron reduction potential of the coordinated anthraquinone moiety functionalized with the imidazole fragment. This can also be attributed to the low luminescence quantum yield of the RuII-polypyridyl complex used. The dynamics of the intramolecular electron-transfer (ET) and PCET processes are studied by using femtosecond transient absorption spectroscopy. The steady- state spectroscopic studies and the results of the time- resolved absorption studies confirm that H- bonded water molecules play a major role in both ET and PCET dynamics as a proton relay in the excited state. The electron- transfer process is followed by a change in the H- bonding equilibrium between AQ and imidazole in acetonitrile solvent, and protonation of AQ(-) water leads to PCET in the presence of water. A slower forward and backward electron- transfer rate is observed in the presence of D2O compared with that in H2O. These results provide further experimental support for a detailed understanding of the PCET process.